PTH-020 Retrospective Cohort Study To Determine The Optimum Frequency Of Surveillance Colonoscopy For Patients With Intermediate Grade Colorectal Adenomas In The Uk. (9th June 2014) - Brenner, A; Greliak, P; Martin, J; Pack, K; Shah, U; Atkin, W
Abstract : Introduction: Colonoscopic surveillance for colorectal cancer (CRC) is widely practiced; however, there remains a lack of evidence to determine appropriate surveillance intervals for individuals at intermediate risk (IR) of CRC. Due to the considerable strain on endoscopic resources and serious cost implications, it is vital to optimise surveillance strategies to ensure colonoscopy is targeted at those who will benefit most. This study examines the frequency of surveillance in patients with intermediate grade (IG) adenomas, aiming to assess whether there is significant heterogeneity in the detection of advanced neoplasia within this group, according to baseline findings and surveillance interval length. Methods: A retrospective cohort design was used in a secondary care setting. 18 UK hospitals were selected based on the availability of electronic patient data suitable for automatic extraction. Endoscopy reports containing Systematised Nomenclature of Medicine codes or words relating to adenomas were identified and linked to corresponding pathology records. These were extracted from hospital databases before being pseudo-anonymised, formatted and uploaded onto an APEX database to be interpreted and coded. Patients were excluded from the analysis if they had no IG adenomas, no baseline colonoscopy, any missing exam dates or conditions affecting CRC risk. Baseline and follow-up visits, and polyp characteristics, were defined using a series of rules developed by the study team. Outcome measures used were advanced adenomas (AA) and CRC; information on these was obtained using follow-up data from external sources, in addition to the hospital data. Analysis of risk of AA and CRC at each follow-up visit, according to baseline findings and interval length, will be performed through the use of descriptive statistics and logistic regression. Approval was obtained from the National Research Ethics Service, Caldicott Guardians and the National Information Governance Board. As it was not feasible to seek patient consent, patient confidentiality was ensured through pseudo-anonymisation of data. Results: Endoscopy and pathology data from over 200, 000 patients was collected and coded, and a large bespoke database was created to store this data. A total of 11, 995 IR patients with a baseline colonoscopy were identified for analysis, 4, 694 of whom have at least one follow-up visit. Conclusion: Analysis of the data is currently in progress. When completed, later this year, conclusions will be drawn on the optimal surveillance intervals for IR patients. The database will also act as a unique resource for further studies involving patients at both low and high risk, and for examining the association between serrated lesions and proximal CRC. Disclosure of Interest: None Declared.